hi i asked about this yesterday but didn't get the help i was looking for exactly. could someone tell me how to figure out 12x + 65y - 1 = 0 and 60y = 150x + 511. i mean could you show how you would figure it out from start to finish with all the workings out. cheers
Hi, I hope this helps.
You have 12x + 65y - 1 = 0 and 60y = 150x + 511.
Rearrange them and you get:
300x+1625y=25 --(2) [this equation (2) is equation (1) multiplied by 25]
300x-120y=-1022 --(4) [this equation (4) is equation (3) multiplied by 2]
*the equations in blue are your original equations.
By elimination method, equate (2) and (4) together to get rid of the 300x they have in common:
What's left will be 1625y-(-120y)=25-(-1022)
= 0.6 or 3/5
substitute y=0.6 into any of the equations to get x. For me, I chose equation (1) as it is simpler:
Hence, x=-19/6 and y= 3/5.
thanks a lot leo and masters, i understand now